2015
DOI: 10.1111/gtc.12221
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel role for Drosophila MESR4 in lipid metabolism

Abstract: Drosophila provides a powerful genetic model to analyze lipid metabolism. Drosophila has an adipose-like organ called the fat body, which plays a crucial role in energy homeostasis. Here, we conducted a fat body-specific misexpression screen to identify genes involved in lipid metabolism. We found that over-expression of a nuclear protein with nine C 2 H 2 type zinc-finger motifs and a PHD-finger, Misexpression suppressor of ras 4 (MESR4), reduces lipid accumulation in the fat body, whereas MESR4 knockdown inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Overexpression of MESR4 alone causes various defects in the adult fly morphology, such as loss of macrocheatae and dorsal thorax cleft (Abdelilah-Seyfried et al, 2000;Pena-Rangel et al, 2002). Recently, it has been shown that overexpression of MESR4 promoted catabolism of neutral fat in Drosophila fat storage organ called fat bodies to release free fatty acids (Tsuda-Sakurai et al, 2015). RNAi-mediated knockdown experiments suggested a role in innate immunity and cellular response to hypoxia (Cheng et al, 2005;Lee et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of MESR4 alone causes various defects in the adult fly morphology, such as loss of macrocheatae and dorsal thorax cleft (Abdelilah-Seyfried et al, 2000;Pena-Rangel et al, 2002). Recently, it has been shown that overexpression of MESR4 promoted catabolism of neutral fat in Drosophila fat storage organ called fat bodies to release free fatty acids (Tsuda-Sakurai et al, 2015). RNAi-mediated knockdown experiments suggested a role in innate immunity and cellular response to hypoxia (Cheng et al, 2005;Lee et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…y w 67c23 (referred to as y w) was used as a control. MESR4 LA00390 has an insertion of P{Mae-UAS.6.11} in the MESR4 gene (Tsuda-Sakurai et al, 2015). A green balancer, CyO chromosome bearing kr-GAL4 and UAS-GFP S65T transgenes (Casso et al, 2000) was used to identify the genotype of embryos.…”
Section: Fly Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The float buoyancy experiments were conducted essentially as described by Reis et al 2010 and Reis 2016 using 30-50 larvae per sample, with initial results confirmed by the method of Hazegh and Reis (2016) . A relationship between the percentage of larvae floating in a buoyancy assay and the percent body fat of the larvae has been established ( Reis et al, 2010 ; Tsuda-Sakurai et al, 2015 ). Thus, in this study obesity is defined by the relative proportion of the larvae floating in the buoyancy assay.…”
Section: Methodsmentioning
confidence: 99%
“…At the cellular level, obesity can be characterized via quantification of the fat body lipid droplet (LD) size and number (Grönke et al, 2005;Musselman et al, 2011). Some researchers have taken advantage of the altered ratio of fat-to-lean body mass to identify genotypes with increased fat content using buoyancy-based genetic screens (Reis et al, 2010;Tsuda-Sakurai et al, 2015). Lipogenesis can be further characterized by the incorporation of labeled carbons from the diet into various lipid classes using mass spectrometry .…”
Section: Introductionmentioning
confidence: 99%